An Overview of Possible Therapeutic Approaches Against Novel Coronavirus Disease 2019 (COVID-19) Pandemic - Hussein, Mohammed; Alsayed, Raghda; Hussain, Zainab; Salih, Nadia; Yousif, Emad (Al-Nahrain Journal of Science, 2020)
The fatal disease coronavirus 2019 (COVID19) is produced by SARS-COV2. It caused a hug global problem due to causing of killing ten thousands of people around the work and almost stopped the world economy causing great economic problem. This is because of the quarantine in many countries around the world. Up to date, researchers believe that COVID19 has transferred from animals like bats or rodents to the humans and spread around the world by person to person direct contact, coughing, or sneezing. Many therapeutic approaches have been utilized to stop this pandemic from spreading around the world hence almost of the strategies showed a moderated results against the virus. In Shanghai doctors used the blood plasma of recovered patients and injected it to the infected patients, this approach has demonstrated positive results against the virus. This review includes a highlighting of some medications which have shown promising results especially if it will link with other type of drugs such as Ivermectin.